The recent advances in surface antibacterial strategies for biomedical catheters. (19th June 2020) - Liu, Lin; Shi, Hengchong; Yu, Huan; Yan, Shunjie; Luan, Shifang
Abstract : This review focus on the recent advances in surface modification strategies of biomedical catheters used to prevent CRIs. Abstract : As one of the most common hospital-acquired infections, catheter-related infections (CRIs) which are caused by microbial colonization lead to increasing morbidity and mortality of patients and life threat for medical staffs. In this case, a variety of efforts have been made to design functional materials to limit bacterial colonization and biofilm formation. In this review, we focus on the recent advances in surface modification strategies of biomedical catheters used to prevent CRIs. The tests for the evaluation of the performances of modified catheters are listed. Future prospects of surface antibacterial strategies for biomedical catheters are also outlined.